2016
DOI: 10.4103/0972-0707.186441
|View full text |Cite
|
Sign up to set email alerts
|

Dental unit waterlines disinfection using hypochlorous acid-based disinfectant

Abstract: Objective:The purpose of the study was to investigate the efficacy of a new disinfectant to disinfect the dental unit waterlines.Materials and Methods:New dental unit waterlines were installed in 13 dental chairs, and biofilm was allowed to grow for 10 days. Disinfection treatment procedure was carried out in the 12 units, and one unit was left untreated. The dental unit waterlines were removed and analyzed using the scanning electron microscope (SEM) (TESCAN VEGA3 SBU).Result:On examination, SEM images showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This follow-up study highlights the importance of using biocides (Alpron and ICX) to clean DUWLs. In literature, the use of various biocides (Hypochlorous acid, Alpron, Sterilox, Bio 2000, Dentosept, Oxygenal and sodium hypochlorite) have been suggested to disinfect DUWLs [35][36][37][38]. However, to meet the CDC/EPA recommended standards (≤500 CFU/mL), dentists should follow the specified protocols for using biocides as suggested by manufacturers of biocides/dental unit.…”
Section: Discussionmentioning
confidence: 99%
“…This follow-up study highlights the importance of using biocides (Alpron and ICX) to clean DUWLs. In literature, the use of various biocides (Hypochlorous acid, Alpron, Sterilox, Bio 2000, Dentosept, Oxygenal and sodium hypochlorite) have been suggested to disinfect DUWLs [35][36][37][38]. However, to meet the CDC/EPA recommended standards (≤500 CFU/mL), dentists should follow the specified protocols for using biocides as suggested by manufacturers of biocides/dental unit.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the result obtained from SEM, it was concluded that usage of disinfectant was found to be effective in the removal of biofilm. Various other disinfectant solutions that are used include hydrogen peroxide, chlorhexidine gluconate, Listerine mouthwash, povidone-iodine and electrochemically activated water [29].…”
Section: Dental Unit Waterline (Duwl) Sterilizationmentioning
confidence: 99%
“…handpieces and triple syringe) after every patient use, and flushing them at the start of the day to reduce overnight or weekend biofilm accumulation. 18…”
Section: Patient Precautions Before Starting Dental Treatment On the Chairmentioning
confidence: 99%